Radio in the Age of AI - V. Basil Hans; Rashmi Ammembala (International Journal of Radio Frequency Innovations, 2026)
Artificial intelligence (AI) is changing the traditional world of radio broadcasting very quickly. It is changing the way material is made, curated, shared, and listened to. This article talks about how AI technologies like machine learning, natural language processing, and automated voice synthesis can be used in radio production and operations. It looks at how AI-powered solutions may make listening more personalised, give real-time audience statistics, automatically generate news, and make smart content recommendations, all of which improve audience engagement and operational efficiency. Broadcasters are using AI- driven automation to offer multilingual programming to a variety of audiences across digital platforms, save production costs, and increase scheduling accuracy. The study also looks at new problems that are coming up, such as worries about authenticity, the ethical use of synthetic voices, data privacy, and the possibility of replacing human talent in broadcasting jobs. The essay talks about how the job of radio professionals is changing in an AI-augmented world by looking at current trends and case examples. It stresses the necessity for hybrid abilities that combine creativity with technology knowledge. The paper contends that instead of supplanting traditional radio, artificial intelligence is reshaping its significance in the digital era allowing it to persist as a vibrant, accessible, and versatile medium within an ever more competitive media landscape.
Keywords: Automation; Personalisation; Radio Broadcasting; and Audience Analytics; artificial intelligence